Back Cover: A Nonenzymatic Hydrogen Peroxide Electrochemical Sensing and Application in Cancer Diagnosis (Small Methods 5/2021). Issue 5 (12th May 2021) - Yu, Yan; Peng, Jinrong; Pan, Meng; Ming, Yang; Li, Yan; Yuan, Liping; Liu, Qingya; Han, Ruxia; Hao, Ying; Yang, Yun; Hu, Danrong; Li, He; et al.
Abstract : In article number 2001212, Yan Yu, Jinrong Peng, Zhiyong Qian, and co‐workers developed a biologically sensitive and efficient H2 O2 electrochemical sensor based on PtNi‐N‐rGO nanocomposites. Using this sensing can successfully capture H2 O2 from cancer cells after fMLP added. This sensing is capable of tumor diagnosis at high sensitivity, fast rate, and cheap.